2006
DOI: 10.1037/1082-989x.11.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Paper or plastic? Data equivalence in paper and electronic diaries.

Abstract: Concern has been raised about the lack of participant compliance in diary studies that use paper-and-pencil as opposed to electronic formats. Three studies explored the magnitude of compliance problems and their effects on data quality. Study 1 used random signals to elicit diary reports and found close matches to self-reported completion times, matches that could not plausibly have been fabricated. Studies 2 and 3 examined the psychometric and statistical equivalence of data obtained with paper versus electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
304
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(312 citation statements)
references
References 20 publications
7
304
0
1
Order By: Relevance
“…First, some participants used paper methods of data collection whereas others used an electronic method. Although it might be thought that the traditional paper diary method would be associated with poor compliance, it has been demonstrated that compliance rates are similar for both paper diary methods and electronic diary methods (Green et al, 2006). Second, the sample size might be criticized as being relatively small (20 per group), and further larger studies are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…First, some participants used paper methods of data collection whereas others used an electronic method. Although it might be thought that the traditional paper diary method would be associated with poor compliance, it has been demonstrated that compliance rates are similar for both paper diary methods and electronic diary methods (Green et al, 2006). Second, the sample size might be criticized as being relatively small (20 per group), and further larger studies are needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 70%
“…Past research has shown that the two methods are compatible, and that compliance rates are similar (Green et al, 2006). The 'Experience Sampling Program' (version 4.0) (Barrett and Feldman, 2000), installed on the palm pilots emitted a signal (bleep) at variable time points within ten equal time intervals between 8am -10pm, over 6 consecutive days.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This process helped both parties gain clarity and enhance the trustworthiness and authenticity of the data. It also exemplifies how the research process can encourage participants to take on a "researcher-like" role and experience the invested outcome of the study (Green, Rafaeli, Bolger, Shrout, & Reis, 2006). This process of gaining clarity by discussing and adding additional notes was undertaken in an informal relaxed manner.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…We took this approach, rather than an event-contingent approach where assessments are recorded after a prespecified event, as reduced burden has been shown to increase participant compliance. 42 This approach was also preferred in a feasibility focus group conducted with nurses from multiple clinical areas and job roles, with ranging levels of seniority to explore issues around the study method and measures. Furthermore, for the variables of interest we deemed reflections at the end-of-shift appropriate as it is unlikely they would vary greatly throughout a shift.…”
Section: Designmentioning
confidence: 99%